2020
DOI: 10.1039/d0cp04694a
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of d–d interactions in density functional tight binding for transition metal ions with a ligand field model: assessment of a DFTB3+U model on nickel coordination compounds

Abstract: DFTB3+U for transition metal systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…One possible improvement is to treat the d/f electrons separately, along the lines of the DFT+U model in materials science 59 or the ligand-field model in the inorganic chemistry literature. 60,61 In a recent explorative study, 62 together with collaborators we have implemented a preliminary version of the DFTB3+U model…”
Section: Several "Burning Issues"mentioning
confidence: 99%
See 3 more Smart Citations
“…One possible improvement is to treat the d/f electrons separately, along the lines of the DFT+U model in materials science 59 or the ligand-field model in the inorganic chemistry literature. 60,61 In a recent explorative study, 62 together with collaborators we have implemented a preliminary version of the DFTB3+U model…”
Section: Several "Burning Issues"mentioning
confidence: 99%
“…Energetics are generally less satisfying, especially when considering different spin states, since interactions among d/f electrons are treated in an averaged fashion in the current tight-binding models. One possible improvement is to treat the d/f electrons separately, along the lines of the DFT+U model in materials science or the ligand-field model in the inorganic chemistry literature. , In a recent explorative study, together with collaborators we have implemented a preliminary version of the DFTB3+U model in which P U ( P I ) is the spin unpolarized (polarized) density matrix element involving the d/f electrons and the usual two-electron integrals are parametrized in terms of the Slater integrals or the Racah parameters . It was found that the additional U contribution indeed improved the splitting between the low-spin and high-spin states in a series of Ni­(II) and Ni­(III) compounds as well as the populations of the 3d orbitals .…”
Section: Several “Burning Issues”mentioning
confidence: 99%
See 2 more Smart Citations
“…The OPBE functional was chosen for this research since it is one of the best DFT functionals for accurate prediction of vibrational frequencies, reaction barriers, spin-state splittings, and geometries. Energies and gradients were calculated using the local density approximation (LDA; Slater exchange and Vosko–Wilk–Nusair (VWN) correlation) with nonlocal corrections due to Handy–Cohen (OPTX exchange), , and Perdew–Burke–Ernzerhof (PBEc correlation) added self consistently . The spin-state splitting predicted by OPBE gives the correct spin ground state in almost all cases, except for the iron–porphyrin with an axial histidine ligand.…”
Section: Theoretical Methodsmentioning
confidence: 99%